COACH AS A DECISION MAKER - Enes Huseinagić; Adnan Hodžić (Sport Scientific And Practical Aspects, 2025)
Research conducted is realized with 25 basketball coaches in Tuzla County with a goal to diagnose success of the making decision process. Problems appeared in this process were lack of information, unreliable data, confusion, insufficient knowledge level of the coach, limited resources, ect. Out of 25 treated basketball coaches, two coaches or in percentage 8% has showed that resolution process isn’t satisfying. 18 coaches or in percentage 72% own very good dexterities when making decisions. For this group of coaches is characteristic that they know the process of making decisions. Five coaches or in percentage 20%, own very good dexterities when making decisions. Research itself has showed that the best answer to uncertain situation in means of effective decision making is professional organizing with an aim to sight unexpected situations and fast adapting to changed state, which in basketball is inevitable. Basketball today demands teams organized with high level of reliability, which represents that coaches have universal competences.